MAKNA PENGALAMAN PASTORAL MAHASISWA DALAM MAGANG DI LINGKUNGAN: STUDI FENOMENOLOGI SOSIAL DI OELNITEP, PAPIN, DAN NAENLULU, KEUSKUPAN ATAMBUA - Kristhoporus Ukat; , Maria Sensi Yerina Molo; Maria Dominica Loe Usfinit; Yohana Aek Klau; Gracina Irmalia Manek; Angela Ravelina Bete; Putry Sandra Vira Klau (LPPM STP St. Petrus Keuskupan Atambua, 2025)
The Community Service Program (PkM) for Pastoral Internship of STP St. Petrus Kefamenanu students was carried out in September 2025 across three communities, Papin, Naen/Lu’lu, and Oelnitep, with the aim of fostering students’ reflective awareness through contextual faith-based service. This program responds to the need for pastoral formation that integrates theology and lived human experience rather than focusing solely on technical activities. This study employs Alfred Schutz’s social phenomenology approach to interpret the meaning of students’ pastoral experiences as encounters of faith that shape reflective and relational awareness. Data were collected through interviews with eight students and three community leaders, accompanied by direct field observation. The results show that the Pastoral Internship serves as a laboratory of faith, nurturing a habitus caritatis, a lifestyle of love grounded in faith reflection and manifested in concrete service. The shared experience between students and parishioners produced a dual transformation: students experienced spiritual growth, while the community underwent renewal of faith through participatory engagement. This program enriches the model of reflective pastoral formation based on social phenomenology, which is highly relevant to the pastoral mission of the local Church in Timor.